An exploratory study on the relationship between involvement and attitude towards tv advertisements with Islamic symbols and purchase intent. - Hamisah Hasan,; Ezhar Tamam,; Jusang Bolong,; Mohd Nizal Mohd Nor,; Azhani Ali, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The exploratory study was conducted to examine the impact of involvement and attitude towards Television (TV) advertisements (ads) with Islamic symbols to that of purchase intent. Specifically the study examines i) the level of involvement towards TV ads, ii) the attitude towards TV ads, iii) the relationship between involvement towards TV ads and purchase intent, iv) the relationship between attitude towards TV ads with and purchase intent. The framework of the study was constructed based on the Elaboration Likelihood Model (ELM) that suggested that the level of consumers’ involvement differ due to their processing of information. The theory also explained that sometimes the use of different cues were able to generate consumers’ high involvement in their information processing. This has thus, contributed significantly to their purchase intent. The study utilized the one group post-test only experimental methods by engaging 76 female subjects from Kuala Lumpur to participate. They were shown four advertisements that have Islamic symbols and asked to answer a set of self-administered questionnaires. The study found that the subjects showed high involvement on ads that used the Islamic symbols of “hijab” and thus have effectively generated positive attitude towards the advertisements. The results also revealed that there was a positive impact between the Islamic symbols on purchase intent.